Effect of zirconia surface treatment using nitric acid-hydrofluoric acid on the shear bond strengths of resin cements - Cho, Jin Hyung; Kim, Sun Jai; Shim, June Sung; Lee, Keun-Woo (The journal of advanced prosthodontics, 2017)
The aim of this study was to compare the surface roughness of zirconia when using Zircos E etching system (ZSAT), applying a nitric acid-hydrofluoric acid compound as a pretreatment agent, and also to compare the shear bonding strength according to different resin cements. ZSAT, air abrasion, and tribochemical silicacoating were applied on prepared 120 zirconia specimens (10 mm in diameter, 7 mm in height) using CAD/CAM. Each 12 specimens with 4 different resin cements (Panavia F 2.0, Rely X Unicem, Superbond C&B, and Hot bond) were applied to test interfacial bond strength. The statistical analysis was performed using SAS 9.1 (SAS Institute Inc., Cary, NC, USA). The results are as follows: after application of the ZSAT on the zirconia specimens, surface roughness value after 2-hour etching was higher than those after 1- and 3-hour etching on SEM images. For Superbond C&B and Rely X Unicem, the specimens treated with ZSAT showed higher shear bond strength values than those treated with air abrasion and tribochemical silicacoating system. Regarding the failure mode of interface over cement and zirconia surface, Rely X Unicem and Hot bond showed cohesive failures and Panavia F 2.0 and Superbond C&B showed mixed failures. Zircos E etching system in zirconia restoration could increase its shear bond strength. However, its long term success rate and clinical application should be further evaluated.